Palaeoenvironmental interpretation of late miocene outcrops (Miri and seria formations) along jalan tutong in brunei darussalam - Roslim, A. (Geological Society of Malaysia, 2020)
Eleven Neogene outcrops (seven of the Miri Formation and four of the Seria Formation) from Brunei Darussalam are described. Detailed stratigraphic columns are presented with special emphasis on the sedimentary sequences, providing insights into the depositional environments. The rocks are comprised mostly of sandstone, claystone and a mix of both lithologies, and are piled up in cycles of coarsening upward successions, which are here interpreted as parasequences. Most sections are characterized by abundant and diverse sedimentary structures, reworked fossiliferous deposits and organic fragments such as ambers and wood remains. Certain beds are rich in fossils: among the macrofossils, the most common are bivalves, gastropods and followed by fish remains (teeth and otholiths), crustaceans, corals and echninoderms, which are abundant at specific locations. Among the microfossils, the most common are foraminifera, which are mostly dominated by either rotaliids or textulariids; the most common genera are Ammonia, Elphidium and Trochammina. Porcelaneous and planktonic foraminifera are rare. Ostracods are also found. Ichnofossils are quite abundant in all sections but are represented mostly by Ophiomorpha and Thalassinoides. In view of the observations, the sections are interpreted as evidence of shallow-marine conditions, in which wave, fluvial and tidal actions strongly influenced the depositional environment. In a few cases, deposition of sediment seems to reflect the transition from wave-dominated to tide-dominated conditions. Our findings indicate that in such shallow marine deposits, the interpretation of sediment type and sedimentary structures alone cannot indicate one specific sedimentary environment, but such observations should include palaeontological evidence to generate more accurate palaeoenvironmental reconstructions. Lastly, our results are discussed in relation to the sedimentary evolution of the region. Â© 2020 Geological Society of Malaysia. All rights reserved.